The Planning System: Market and Centralization - Igor Yu. Varyash (Review of Business and Economics Studies)
The article aims to outline approaches to the study of a harmonized model of forecasting, strategic planning and expectations of business communities. In the Introduction, the idea of transformation of planning to the dominance of the network approach instead of the dominance of centralization is substantiated. Materials and methods. The key aspects of the expediency of applying the experience of centralized planning under state ownership, providing information resources and applying modern high-tech methods for collecting, processing and analytically presenting materials to improve the effectiveness of preventive decisions, introducing a backbone component of leading indicators into network planning are considered. Results and discussion. The article includes innovative proposals for using the technology of leading indicators and increasing the role of horizontal links in planning with their help. It is concluded that it is necessary to shift the semantic emphasis in discussions on the development of planning to the harmonization of planning, forecasting and development parameters expected by business communities.